Relationship between blood lactate and hyperventilation during high-intensity constant-load exercise in heat - Chiba, T.; Ishii, H.; Takahashi, S.; Yano, T. (Biology of Sport, 2011)
The purpose of this study was to examine the relationship between hyperventilation and increase in blood lactate during high-intensity constant-load exercise in heat and normal conditions. Seven male volunteers exercised for 10 min on a cycle ergometer at 80% ·VO2max in heat (40ºC, 50% relative humidity: HT) and normal conditions (20ºC, 50% relative humidity: CON). Oxygen uptake, carbon dioxide output, ventilation, blood lactate and blood electrolytes (K+, Na+, Cl-) were measured in HT and CON. We found that ventilation was significantly higher during exercise in HT compared with CON (p<0.05) and RER tends to be higher in HT than in CON. Blood lactate was significantly higher at 3 min during exercise in HT compared with CON (5.96 ± 0.57 mEq·l-1 5.00 ± 0.28 mEq·l-1, p<0.05). Change in strong ion difference, which affects deltaHCO3- in blood significantly, was lower at 5 min during exercise in HT compared with in CON (p<0.05). These results suggest that hyperventilation during exercise in heat would induce lower HCO3- in blood and consequently would result in an increase in blood lactate at an earlier time during high-intensity exercise in heat. It was concluded that hyperventilation during short-term high-intensity exercise in heat is temporarily associated with an increase in blood lactate.